2000
DOI: 10.1046/j.1469-8137.2000.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ozone exposure on growth and photosynthesis of beech seedlings (Fagus sylvatica)

Abstract: The effects of ambient and elevated ozone levels on growth and photosynthesis of beech (Fagus sylvatica) were studied by exposing seedlings in open-top chambers for one growing season to three treatments : charcoal-filtered (CF), non-filtered (NF) and non-filtered air with addition of ozone (30 ppb ozone) on clear days for 8-10 h d −" (NFj). Ambient levels were relatively low and accumulated to an AOT40 (accumulated exposure over a threshold of 40 ppb) of 4055 ppb h (for the period 23 Apr-30 Sept). The NFj cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 35 publications
4
23
0
Order By: Relevance
“…Cinnamonum campora (Feng et al, 2011), Viburnum lantana (Calatayud et al, 2010), poplar (Bohler et al, 2010), aspen (Noormets et al, 2001) and beech (Bortier et al, 2008). Also, Fv 0 /Fm 0 and F PSII but not qP were significantly reduced by E-O 3 , suggesting that E-O 3 increased light energy dissipation of the antenna pigment, thus leading to a reduction in the efficiency of excitation energy captured by the open PSII reaction center, but no change on the proportion of open PSII reaction center.…”
Section: Discussionmentioning
confidence: 95%
“…Cinnamonum campora (Feng et al, 2011), Viburnum lantana (Calatayud et al, 2010), poplar (Bohler et al, 2010), aspen (Noormets et al, 2001) and beech (Bortier et al, 2008). Also, Fv 0 /Fm 0 and F PSII but not qP were significantly reduced by E-O 3 , suggesting that E-O 3 increased light energy dissipation of the antenna pigment, thus leading to a reduction in the efficiency of excitation energy captured by the open PSII reaction center, but no change on the proportion of open PSII reaction center.…”
Section: Discussionmentioning
confidence: 95%
“…Ozone might decrease photosynthesis through reductions in stomatal conductance, but in this study, decreases in photosynthesis are larger in magnitude than decreases in conductance, suggesting that an additional mechanism is causing observed decreases in photosynthesis. Many studies (Francini et al 2007;Noormets et al 2001;Fiscus et al 1997;Heagle et al 1996;Sharma et al 2003;Bortier et al 2000) similarly found that O 3 -induced differences in photosynthesis were the result of nonstomatal factors, potentially driven by either photosystem oxidation, limiting energy for RuBP regeneration, or decreased efficiency of Rubisco due to direct enzyme oxidation or reduced CO 2 transport to the enzymes. The decreases in J max and V cmax observed in this experiment suggest that O 3 reduces the biochemical capacity to fix CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the ability of a plant to regulate leaf water loss in most situations is singly controlled by stomatal behavior (Cowan 1978). Oxidants like O 3 are capable of damaging the guard cells of stomata, the functioning of cellular membranes regulating diffusion and electron transport, and enzymes involved in the carboxylation process (Bortier et al 2000;Kellomaki and Wang 1997;Reichenauer et al 1997). Since leaf water loss depends primarily on a single plant-controlled parameter and photosynthesis depends on a series of factors, O 3 damage to any of these processes at unequal rates or magnitudes will cause photosynthesis and transpiration to become decoupled, with potentially large impacts on global carbon and water cycling.…”
Section: Introductionmentioning
confidence: 99%
“…O 3 -induced growth reductions, reduced C assimilation and allocation, leaf chlorosis and early leaf fall have been reported for beech in several studies (Pearson and Mansfield 1993;Mortensen et al 1995;Krause and Höckel 1995;Mikkelsen and HeideJørgensen 1996;Braun and Flückiger 1995;Bortier et al 2000b). The objective of this study was to assess the response of growth and photosynthetic processes (gas exchange and chlorophyll fluorescence) of young beeches to O 3 and to compare their response in relation to the AOT40 and calculated O 3 uptake.…”
Section: Introductionmentioning
confidence: 92%